Software Development of Palm Oil Seed Authentication System Based on Ultrasonic Waves - Pratopo, Lukito Hasta; Thoriq, Ahmad; Ciptaningtyas, Drupadi; Nanda, Muhammad Achirul; Fahrizi, Ahmad Luthfi; Hidayat, Darmawan; Masrukan; Maskromo, Ismail (Jurnal Keteknikan Pertanian, 2025)
Fake palm oil seeds pose a substantial economic threat, which makes their authentication crucial. However, distinguishing between genuine and fake seeds remains a challenge. This study explored the potential of ultrasonic technology to measure shell thickness as a distinguishing factor based on the reported variations between the two types. Ultrasonic wave measurement software was developed using Arduino Uno to facilitate the analysis. The results highlight the complexity of accurately measuring the seed shell thickness owing to high attenuation. Micro-CT imaging confirmed the presence of pores within the seed structure, which significantly scattered and absorbed ultrasonic waves, limiting the penetration depth and accuracy. Despite these obstacles, the developed software exhibited promising capabilities, accurately determining the thickness or propagation speed with a high-resolution time-of-flight measurement of up to 62.5 nanoseconds. Additionally, the software is capable of sampling ultrasonic signals at frequencies up to 178 kHz. Although the software performs well under specific conditions, further advancements in ultrasonic technology are necessary to mitigate porosity-related limitations and enhance the effectiveness of seed authentication methods, particularly in transducer selection and measurement techniques such as Harmonic or QSC testing.